Knowledge of surgical management of hyperhidrosis among primary care physicians and the general public. (7th January 2022) - Lee, Andy Chao Hsuan; Ferguson, Mark K
Abstract: OBJECTIVES: Our study examined attitudes towards initial management of hyperhidrosis, willingness to seek surgical consultation and knowledge of an appropriate specialty for surgical consultation among primary care physicians and the general public. METHODS: An online survey was sent to all general medicine and paediatric residents and attending physicians at our academic medical centre. Participants were provided with a clinical scenario of palmar hyperhidrosis and were asked to select among initial management options and preferences for surgical consultation if patients failed non-operative management. To assess the general public's perspective, workers from Amazon Mechanical Turk were recruited to complete a similar survey. RESULTS: The majority of primary care physicians (31/53; 58%) would prescribe topical aluminium chloride for palmar hyperhidrosis, whereas 28 of 53 (53%) would refer such patients to dermatology. Twenty-three of 53 (43%) physicians would refer such patients to surgery if conservative management failed: 18 (78%) to plastic surgery, 4 (17%) to general surgery and none to thoracic surgery. The majority of workers (130/205; 63.4%) would seek primary care treatment for palmar hyperhidrosis. Over half (113/205; 55%) would seek surgical consultation if conservative management failed: 65 (58%) general surgery and 15 (13%) neurosurgery, with only 8 (7%) selecting thoracic surgery. CONCLUSIONS: Neither primary care physicians nor the general public recognize the role of thoracic surgeons in managing primary focal hyperhidrosis when medical management fails. Education of physicians and the public may mitigate this knowledge gap. Abstract : Primary focal hyperhidrosis is an idiopathic condition characterized by excessive sweating, usually of the hands, axillae and/or feet, well beyond physiological demands.